2023
DOI: 10.1007/s00248-023-02230-w
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobiome of Bats in the American Southwest Is Structured by Geography, Bat Species, and Behavior

Abstract: Bats are widespread mammals that play key roles in ecosystems as pollinators and insectivores.However, there is a paucity of information about bat-associated microbes, in particular their fungal communities, despite the important role microbes play in host health and overall host function. The emerging fungal disease, white-nose syndrome, presents a potential challenge to the bat microbiome and understanding healthy bat-associated taxa will provide valuable information about potential microbiomepathogen intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…They concluded that caves with active bat hibernacula supported bat-related fungi, while caves without bats, but abundant arthropods, contained entomopathogenic fungal genera. The conclusions of this and other papers [ 58 , 64 , 74 – 76 ] were confirmed in this study on biofilms from gypsum caves.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They concluded that caves with active bat hibernacula supported bat-related fungi, while caves without bats, but abundant arthropods, contained entomopathogenic fungal genera. The conclusions of this and other papers [ 58 , 64 , 74 – 76 ] were confirmed in this study on biofilms from gypsum caves.…”
Section: Discussionsupporting
confidence: 90%
“…The entrances to the gypsum caves are open, allowing the entry and roosting of bats. Therefore, the high number of fungal genera identified in the bat microbiome by a few authors [ 45 , 64 , 74 ], and their finding in cave biofilms, are not surprising. Furthermore, Hathaway et al [ 58 ] reported that bat microbiomes have an influence on the cave wall microbiome, and Kokurewicz et al [ 75 ] stated that the number of bats was a key factor determining the occurrence of fungal spores at the hibernation site.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are various other microbial genera that have shown inhibition ability but are still overlooked. Fungi are among the often disregarded species that have also shown promise in pathogen inhibition [84][85][86]. For example, North American bat species resistant to WNS exhibit a more diverse cutaneous mycobiome compared to WNS-susceptible species [86].…”
Section: Are Probiotics the Solution To Lethal Skin Disease In Wildlife?mentioning
confidence: 99%